Serum Cgrp Can Serve as A Clinically Useful Biomarker for Differentiating Migraine from Tension-Type Headache - Batoul Munir Abbas; Ghosoon Ghanim Kaem; Haider Shafi Hussein (International Journal of Medical Science and Dental Health, 2026)
Background: Migraine and tension-type headache (TTH) are the two most prevalent primary headache disorders and remain a major cause of disability worldwide. Despite their high prevalence, differentiating these conditions in clinical practice still relies primarily on symptom-based diagnostic criteria. The present study aimed to evaluate serum CGRP concentrations in patients with migraine, patients with tension-type headache, and healthy individuals. Methods: This cross-sectional study included 100 subjects, recruited from November 2025 to March 2026: 35 migraine patients, 35 tension-type headache patients, and 30 healthy controls. Diagnosis of migraine and TTH was made by a consultant neurologist according to established clinical criteria. Serum CGRP levels were measured with a sandwich enzyme-linked immunosorbent assay (ELISA). Results: The serum concentrations of CGRP were significantly different between the three study groups (P < 0.001). The highest CGRP levels were observed in migraine patients (355.57 ± 86.29 pg/mL) followed by TTH patients (220.59 ± 42.25 pg/mL) and the lowest in healthy controls (171.27 ± 32.62 pg/mL). CGRP levels were significantly higher in migraine patients than TTH patients (P<0.001). Thus, migraine is associated with increased trigeminovascular activation. Serum CGRP showed good diagnostic performance in the ROC curve analysis with AUC of 0.879, optimal cutoff value of 221.47 pg/mL, sensitivity of 67.14%, and specificity of 96.67%. The serum CGRP could discriminate patients with primary headache disorders from healthy controls, as confirmed by ROC curve analysis. Conclusions: Serum CGRP is markedly elevated in migraine compared with both tension-type headache and healthy controls, reflecting its central role in migraine pathophysiology. Its high diagnostic accuracy, particularly its excellent specificity, highlights its potential as a clinically useful biomarker for differentiating primary headache disorders and supports its future integration into diagnostic and therapeutic strategies.